GUIDELINE FOR DEVELOPMENT OF THE PUBLIC LIBRARY ADMINISTRATION SANPATONG DISTRICT CHIANG MAI PROVINCE - ใจหน้อย, โชติดารา; ปาจา, ถนอม (Community and Social Development Journal, 2018)
The objectives of this research were 1) to study the state and problem of The public library administration, San Pa Tong District, Chiang Mai Province, and 2) to study guidelines for developing the public library administration, San Pa Tong District, Chiang Mai Province.The research findings showed that in there was no a systematic administration; staffs were lacked of knowledge and understanding in their jobg; the building and place were compacted; the number of computers was not enough for the users, some were out-of-order, and the staffs had no skill in using computers are.The guidelines for developing the administration of public library San Pa Tong District.